Use of a Bubble Curtain to Reduce Fish Mortality during Explosive Demolition of Licks and Dam 26, Mississippi River - Thomas M. Keevin; Gregory L. Hempen; David J. Schaeffer (International Society of Explosives Engineers, 1997)
In an attempt to reduce the potential for fish mortality during the explosive demolition of Locks and Dam 26, Mississippi River, the U.S. Army Corps of Engineers, St. Louis District explored the use of a bubble curtain to reduce the fish kill radius of underwater explosions. Bubble curtains are walls of bubbles rising from a bottom-resting bubbler manifold supplied with compressed air. Demolition engineers have long been aware of the attenuating properties of air bubbles in water. As such, air curtains have been routinely used to protect underwater structures from damage by underwater explosive shock waves. However, their use in protecting aquatic resources during full-scale explosive demolition projects was untested.